Design of smart lubricants using the inverse ferrofluid approach. (February 2022) - Sahoo, R.; Ussa-Aldana, P.; Lancon, D.; Rondelez, F.; Morillas, J.R.; Hidalgo-Alvarez, R.; de Vicente, J.
Abstract: A new formulation is proposed to lubricate tribopairs in extreme conditions where the amount of lubricant is small and the lubricating region highly confined. It is composed of non-magnetic solid lubricants dispersed in an oil-based ferrofluid. When this inverse ferrofluid (IFF) is magnetically activated, the lubricant particles are subjected to magnetophoretic forces. By using appropriate magnetic field gradients, they can be driven to the region of interest and thus control the friction locally. The rheological and tribological performances of three IFF formulations are evaluated in several conditions of applied magnetic field strength and shear flow rates. Highlights: Field-responsive inverse ferrofluids are fabricated by dispersion of solid lubricants. PTFE, Silica and MoS2 nanoparticles are dispersed in PAO-based ferrofluids. Friction in tribopairs can be controlled by the superposition of localized magnetic field gradients. The particle size dictates the friction mechanism.